2013
DOI: 10.1177/1073191113490790
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Mindfulness-Based Interventions – Teaching Assessment Criteria (MBI:TAC)

Abstract: Background. The assessment of intervention integrity is essential in psychotherapeutic intervention outcome research and psychotherapist training. There has been little attention given to it in mindfulness-based interventions research, training programs, and practice. Aims. To address this, the Mindfulness-Based Interventions: Teaching Assessment Criteria (MBI:TAC) was developed. This article describes the MBI:TAC and its development and presents initial data on reliability and validity. Method. Sixteen assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(165 citation statements)
references
References 22 publications
2
156
1
6
Order By: Relevance
“…The integrity and fidelity of each MBP is maintained by ensuring that all the curriculum elements for the particular program are included as intended (adherence) and that curriculum elements are not added which do not belong to the particular program form (differentiation) (Crane et al 2013). It is critical that the curriculum employed and the particular MBP title match each other.…”
Section: The Essential ('Warp') Elements Of Mbpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integrity and fidelity of each MBP is maintained by ensuring that all the curriculum elements for the particular program are included as intended (adherence) and that curriculum elements are not added which do not belong to the particular program form (differentiation) (Crane et al 2013). It is critical that the curriculum employed and the particular MBP title match each other.…”
Section: The Essential ('Warp') Elements Of Mbpsmentioning
confidence: 99%
“…These competencies are described and can be assessed using the Mindfulness-Based Interventions: Teaching Assessment Criteria (MBI:TAC), which has shown promising evidence as a reliable and valid tool (Crane et al 2012(Crane et al , 2013. The six teaching competence domains within the MBI:TAC are coverage, pacing and organization of the session curriculum; specific interpersonal relational skills; skilful guiding of formal mindfulness meditation practices; specific methodologies for conveying the course themes through interactive inquiry, group dialog and didactic teaching; and effective holding of the group teaching/learning environment.…”
Section: The Teachermentioning
confidence: 99%
“…For example, although there are currently attempts to disseminate best-practice and assessment guidelines for MBI teachers (see Crane et al, 2011;Crane et al, 2013), as yet, Arguably, the most commonly reported integration issue relating to MBIs is that there remains a lack of consensus within psychology in terms of what defines the mindfulness construct (see Chiesa, 2012;Kang & Whittingham, 2010). Many of the issues in this debate relate to the extent to which Western psychological depictions of mindfulness are consistent with traditional Buddhist perspectives.…”
Section: Clinical Integration Issuesmentioning
confidence: 99%
“…This is a particularly important point because there is growing concern among both academicians and clinicians that some MBI instructors may lack the necessary grounding in this respect. For example, although there are currently attempts to disseminate best-practice and assessment guidelines for some MBI teachers [12], as yet, there are no dedicated regulation and accreditation bodies to stipulate minimum competency levels for MBI instructors [3]. Indeed, MBI instructors can have as little as 12 months' mindfulness practice and teaching experience following completion of a single 8-week course [2,3].…”
Section: Adverse Effects Of Mindfulness: the Empirical Research Litermentioning
confidence: 99%